(3eNJUQ aj UfGYI GdWHs - (3eMeO GafOj GdYWGQs ((3eMeO Hf bWH GdWHjH s)
(3ChdgG (B:s
(3fMeO Gddg Ydi eG gOGfG SHjd GdQTGO hHYO agPG eNJUQ ai UfGYI GdWH CdaJg dHYV GdeJYdejf GdbSe GdChd ai CUhd JQcjH GdGOhjI s
(3BNQgG (B:s
(3hcPdc ef YQV dg GdahdfL GdUhH dGjQUO dg GdhbJ hEfeG jYed HgPg GdGNJjGQGJ YfO EJSGY GdhbJ hNha GdJTfjY hdjcf gPG BNQ cdGefG ai gPG GdeNJUQ s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdJGSYI hGdYTQhfs
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(568) s
Keywords: (3GdWHs